Literatura policial e ficção científica na Argentina do século xix: Eduardo L. Holmberg - Andrea Pezzè (e-cadernos ces)
The purpose of this article is to portray the eccentric figure of the Argentinean writer Eduardo L. Holmberg, focusing in particular on two of his late 19th century works - which can be classified as science fiction and detective stories - and relating them to distinctive features of Argentina, while also framing them against the background of the most recent studies on biopolitics and social control. First of all, we will retrospectively analyze the canon of science fiction and detective stories that, according to Ricardo Piglia, began in Argentina with the writings of Jorge Luis Borges (i.e., between the 1930s and 1940s). Later, we will dwell on the theoretical analysis of the role of the State, through the studies of biopolitics by Foucault, Agamben and Esposito, and the management of scientific knowledge by the ruling power depicted in “Horacio Kalibang o los autómatas” and La bolsa de huesos.